Case Study Research in ELT and Applied Linguistics: Trends, Contributions and Challenges - Pandey, Gopal Prasad (Nepalese Linguistics, 2025)
This article critically examines ‘case study research’ in English Language Teaching (ELT) and Applied Linguistics, tracing its historical roots, theoretical bases, and methodological orientations. Employing a qualitative narrative review design, it synthesizes key perspectives and discussions from the major works in the field. The article outlines definitions, types, features, issues, trends, and applications of case studies in ELT. Findings indicate that case studies are particularistic, descriptive, and heuristic, offering rich, contextualized understandings of the classroom situations and learner-teacher interactions. Current trends include a shift from single to multiple-case designs, the rise of longitudinal research, the integration of mixed methodologies, micro-analytic analyses of classroom discourse, and a growing focus on identity, agency and multilingual practices. Despite its limitations related to generalizability and subjectivity, case study research remains vital for developing theory and fostering pedagogical innovation in ELT.